2008
DOI: 10.1128/cvi.00355-07
|View full text |Cite
|
Sign up to set email alerts
|

Increased Synthesis of Anti-Tuberculous Glycolipid Immunoglobulin G (IgG) and IgA with Cavity Formation in Patients with Pulmonary Tuberculosis

Abstract: Tuberculous glycolipid (TBGL) antigen is a cell wall component of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…Moreover, by using ROC analysis, we found that anti-TDM-M and anti-TBGL IgG had similar area under the curve (AUC), but AUC of anti-TBGL IgG improved when MAC positive subjects were excluded. We also noticed that the average anti-TBGL titers and the proposed cut-off levels appear to vary according to severity of the disease and the origin of the studied subjects [6,7,[28][29][30][31].…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Moreover, by using ROC analysis, we found that anti-TDM-M and anti-TBGL IgG had similar area under the curve (AUC), but AUC of anti-TBGL IgG improved when MAC positive subjects were excluded. We also noticed that the average anti-TBGL titers and the proposed cut-off levels appear to vary according to severity of the disease and the origin of the studied subjects [6,7,[28][29][30][31].…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Anti-M. tuberculosis IgG antibodies have been shown to increase in patients with active disease (3,11,13,16). While the function of anti-M. tuberculosis antibodies in providing protective immunity is still under investigation, it has been proposed that they may be utilized as a diagnostic marker of active disease (1,2,7).…”
mentioning
confidence: 99%
“…Recently, we reported the increased synthesis of anti-TBGL IgG in relation to cavity formation in pulmonary tuberculosis and elevated titers of C-reactive protein, which suggest that TBGL IgG could reflect inflammation in active pulmonary TB patients. (Mizusawa et al 2008). Additionally, the anti-TBGL antibody is not influenced by prior BCG vaccination (Nabeshima et al 2005).…”
Section: Discussionmentioning
confidence: 94%